Phytochemical and Antimicrobial Screening of Root Extracts of Carica papaya - Isaac, Aremu Olusola; Adekoya, Abdulganiyu (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Resistance to antimicrobial agents has been on increase in recent time due to a number of factors. There is the need to explore new agents to address the rising failure of some of the existing antimicrobials to therapy. This work is designed to confirm the folklore cla im of the antimicrobial activity of the root extract of the plant Carica papaya. The antimicrobial activity of ethanol extract of male Carica papaya (EMCP), female specie (EFCP) collected at 8.00a.m were tested against some selected bacteria and fungal isolates namely Pseudomonas aeruginosa, Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae and Staphlococcus a u r eu s and Candida albicans respectively. The antimicrobial activity were evaluated using cup plate diffusion method. The root ext racts of the plant were also screened phytochemically for the presence of secondary metabolites. The two ext racts, EFCP and EMCP exhibited certain degree of antimicrobial activity from concentration of 62.5mg/ml to 1000mg/ml .The result further indicated some form of simila rity in antimicrobia l activity for both EMCP and EFCP at most concentrations tested. The Extracts of both EMCP and EFCP contains Saponin, Flavonoid, and Tannins in pronounced amount. They also contain Akaloids, anthraquinones, anthocyanide in moderate amount. The antimicrobial activity of EMCP and EFCP was however, lower than that of ciprofloxacin and clotrimazole that were used as reference standards